Improving Accuracy of Complex Network Modeling Using Maximum Likelihood Estimation and Expectation-Maximization - Jahanpour, Ehsan; Chen, Xin (Discontinuity, Nonlinearity, and Complexity, 2026)
Structure of a complex network provides important information about its performance and may be used to predict changes in network performance. Degree distributions are used to model the network structure. Four degree distributions, including the power law, Weibull, Poisson, and negative binomial, are applied in this research to three complex networks, the Krebs, HIV, and Power Grid networks. To improve accuracy of network modeling, the maximum likelihood estimation method and expectation-maximization algorithm are used to estimate parameters of the four degree distributions. Several statistical analyses and a simulation study are conducted to determine which degree distribution best describes the network structure. The results show that the degree distributions with two descriptive parameters, Weibull and negative binomial, provide better estimations than the onedescriptive-parameter degree distributions, power law and Poisson.